Analysis of the risk factors that determine composite graft survival for fingertip amputation. (December 2018) - Eo, SuRak; Doh, GyeongHyeon; Lim, SooA; Hong, Ki Yong
The composite graft is the only surgical method that is able to maintain digital length and provide soft tissue coverage without donor site morbidities in microsurgically non-replantable fingertip amputations. This study aimed to explore the risk factors that determine the survival of composite grafts. Clinical characteristics associated with graft survival were retrospectively analysed by a comparison between the graft survival and failure groups. Of 94 patients who underwent a composite graft for fingertip amputation, the graft survived in 84 (89%). Surviving grafts showed reperfusion within 1 week. Multivariate analysis revealed that graft failure was independently associated with a crushing injury. Based on the risk factors from the comparison analyses and a review of previously published studies, a cutting injury, grafting the injured finger within 5 hours of injury, and being a non-smoker are associated with good results. In these circumstances, excellent outcomes with a high success rate can be achieved by composite graft in most adult patients as an alternative treatment to microsurgical replantation. Level of evidence: IV